Timing of the triggering action of shooting in relation to the cardiac cycle. - Helin, P (1987)
The purpose of this study was to verify the timing of triggering in relation to the cardiac cycle in shooting. The test subjects were six Finnish rifle and pistol champions as well as three beginners at shooting. The electrical activity of the trigger finger muscle (m. flexor digitorum superficialis; surface electrodes) and the heart cycle were fed into a two-channel x-t recorder. The movements of the gun were recorded using a laser technique and, at the same time, cardiac cycles were also monitored. Results showed that the champion shooters triggered during diastole whereas the beginners triggered both during diastole and systole. The results of those beginners triggering during diastole were better than those triggering during systole.